Aspen-Hysys Simulation Of Sulfuric Acid Plant - Sultana, Sujala T; Amin, M Ruhul (Journal of Chemical Engineering, 2012)
This work presents a theoretical investigation of the simulation of Sulfuric acid process plant. In the production of the acid in contact process liquid sulfur is sequentially oxidized to Sulfur tri oxide via an exothermic reaction which is absorbed by 98% Sulfuric acid in an absorption tower. In this research Aspen One V7.2 has been successfully used to design every sub-process of the sulfuric acid plant in one integrated environment. In order to simulate the process as accurately as possible COM thermo was selected as advanced thermodynamics. Electrolyte NRTL and Peng-Robinson were used for liquid and vapor phase respectively as fluid package and HYSYS properties were used for simulation. The simulation of sulfuric acid process included automatic chemistry generation and the capacity of handling electrolyte reactions for all unit models. Aspen-HYSYS provides specialized thermodynamics models and built-in data to represent the non-ideal behavior of liquid phase components in order to get accurate results. Material and energy flows, sized unit operations blocks can be used to conduct economic assessment of each process and optimize each of them for profit maximization. The simulation model developed can also be used as a guide for understanding the process and the economics, and also a starting point for more sophisticated models for plant designing and process equipment specifying. DOI: http://dx.doi.org/10.3329/jce.v26i1.10182 JCE 2011; 26(1): 47-49